Effect of the Human Amniotic Membrane on the Umbilical Vein Endothelial Cells of Gestational Diabetic Mothers: New Insight on Inflammation and Angiogenesis - Pipino, Caterina; Bernabé-García, Ángel; Cappellacci, Ilaria; Stelling-Férez, Javier; Di Tomo, Pamela; Santalucia, Manuela; Navalón, Carlos; Pandolfi, Assunta; Nicolás, Francisco José (Frontiers in Bioengineering and Biotechnology, 2022)
One of the most relevant diabetes complications is impaired wound healing, mainly characterized by reduced peripheral blood flow and diminished neovascularization together with increased inflammation and oxidative stress. Unfortunately, effective therapies are currently lacking. Recently, Amniotic Membrane (AM) has shown promising results in wound management. Here, the potential role of AM on endothelial cells isolated from the umbilical cord vein of gestational diabetes affected women (GD-HUVECs), have been investigated. Indeed, GD-HUVECs, in vivo exposed to chronic hyperglycemia during pregnancy, compared to control cells (C-HUVECs) have shown molecular modifications of cellular homeostasis ultimately impacting on oxidative and nitro-oxidative stress, inflammatory phenotype, Nitric Oxide (NO) synthesis and bioavailability, thus representing a useful model for studying the mechanisms potentially supporting the role of AM in chronic non-healing wounds. In this study, the anti-inflammatory properties of AM have been assessed using a monocyte-endothelium interaction assay in cells pre-stimulated with Tumor Necrosis Factor-α (TNF-α) and through vascular adhesion molecules expression and membrane exposure, together with the AM impact on Nuclear Factor kappa-light-chain-enhancer of activated B cells (NF-kB) pathway and NO bioavailability. Moreover, GD-HUVEC migration and tube formation ability were evaluated in the presence of AM. Results showed that AM significantly reduced TNF-α stimulated monocyte-endothelium interaction and the membrane exposure of the endothelial Vascular and Intracellular adhesion molecules (VCAM-1 and ICAM-1, respectively) in both C- and GD-HUVECs. Strikingly, AM treatment significantly improved vessel formation in GD-HUVECs and cell migration in both C- and GD-HUVECs. These collective results suggest that AM positively affects various critical pathways in inflammation and angiogenesis thus providing further validation for ongoing clinical trials in diabetic foot ulcer.